Open and percutaneous pediatric tracheostomy: comorbidities and in-hospital mortality - Jeffrey Schemm; David O'Neil Danis; Daniel Howard; Erika Rodriguez; Kaylin Dong; Sherwin Fazelpour; Jessica R. Levi (SpringerOpen, 2023)
Abstract Background Tracheostomy procedures are used to establish a surgical airway in patients when non-invasive methods fail to offer adequate support. In pediatric patients, this procedure is relatively rare, and data on patients is scarce, limiting the ability of physicians to contextualize patient outcomes and identify those most at risk. This can be crucial, as research has shown that early tracheostomy in pediatric patients may improve clinical outcomes. The objective of this study is to characterize the comorbidities of pediatric patients undergoing open and percutaneous tracheostomies and examine their association with in-hospital mortality, as well as to compare patient demographics and comorbidity frequency between the two approaches. The 2016 Kids' Inpatient Database was used to identify patients younger than 21 with ICD-CM-10 codes for open or percutaneous tracheostomies to determine demographic characteristics and identify the most frequent comorbidities in these patient cohorts. Results A weighted total of 5229 cases were analyzed. Congenital cardiopulmonary defects, newborn respiratory diseases, and traumatic lung or brain injury were the most common comorbidities for tracheostomy patients. In open tracheostomies, there was an increased likelihood of in-hospital mortality in patients aged less than one (OR = 2.2; 95% CI, 1.6-3.0) and in patients with atrial septal defects (OR = 1.9; 95% CI, 1.5-2.5), patent ductus arteriosus (OR = 2.5, 95% CI, 2.0-3.3), bronchopulmonary dysplasia (OR = 2.1; 95% CI, 1.6-2.8), and acute kidney injury (OR = 5.6, 95% CI, 4.3-7.2). Trauma-related comorbidities were more common in patients who underwent percutaneous procedures and were not associated with an increased likelihood of mortality. Patient age < 1 was associated with an increased risk of in-hospital mortality in both the open (OR = 2.2; 95% CI, 1.6-3.0) and percutaneous (OR = 2.3, 95% CI (1.3-3.9) approaches. Conclusion There are many indications for pediatric tracheostomy, and patients often present with complicated disease profiles and complicated courses of care. Broadly, we found that congenital cardiopulmonary defects were associated with a higher likelihood of in-hospital patient mortality, especially in younger patients undergoing an open-approach procedure. Patients undergoing a percutaneous-approach procedure were more likely to have trauma-related comorbidities such as pneumothorax or brain hemorrhage that were not associated with in-hospital mortality.